Long –Run relationship between population growth and economic growth in Nigeria (Lapai Journal of Economics, 2020)
This research work analyzes the impact of population growth on economic growth in Nigeria by using time series data sourced from central bank statistical bulletin from 1981 to 2016 for Nigeria. The ordinary least square (OLS) technique was employed to estimate the influence of the explanatory variables.it was found that co-efficient [R2] of 40% variation in economic growth was explained by the variation in the independent variables and population growth has positively and significantly affects gross domestic product over the period of the study.Other additional explanatory variable like government expenditure on health is negatively related to economic growth according to the results. To determine the long-run relationship between the two variables, Augmented Dickey Fuller (ADF) test found that the two series were stationary. The ECM result revealed that population growth and economic growth had long-run relationship. The research concludes by recommending that government should adopt policies that will promote human capital development and make the teeming population more productive to further boost the economy.